An evaluation of the effectiveness of the new primary school mathematics curriculum in practice - Gomleksiz, Mehmet Nuri; Bulut, Ilhami (Edam, 2007)
The aim of this study is to determine and compare the views of primary school teachers on the implementation and effectiveness of the new primary school mathematics curriculum. For that aim, a 32-item Likert-type Mathematics Curriculum Scale was developed. The reliability of the scale was tested through Cronbach Alpha (.98), Spearman-Brown (.93) and Guttman split half (.93) and the scale was found to be reliable. The scale includes four sub-scales. The population includes 792 classroom teachers working in 64 pilot schools where the new primary school mathematics curriculum was in trail in Istanbul, Ankara, Izmir, Kocaeli, Van, Hatay, Samsun, and Bolu. The data were analyzed in terms of city, classroom, gender, reaching experience, education level, and student number variables. Independent samples t-test, Kruskal Wallis H test, variance analysis, Mann Whitney U, Scheffe, and LSD tests were used to analyze the data. Statistically significant differences were found between the views of the teachers in terms of city, classroom, gender and student number variables. It was determined that the learning attainments, content and teaching-learning activities in the new mathematics curriculum were found to be effective by the teachers. But the evaluation part of the new curriculum was not found to be effective in practice. Teachers are advised to have systematic and effective in-service seminars to learn and use the evaluation techniques aimed at the new primary school mathematics curriculum.
Keywords: primary school; new primary school mathematics curriculum; student-centered instruction; constructivism